Factors influencing the occurrence of exclusive breastfeeding failure in six-month-old infants - Nathalia, Ayu; Rahmawati, Dwi; Nastiti, Kunti; Salmarini, Desilestia Dwi (Health Sciences International Journal, 2024)
Background: Mother's milk is the best food for babies aged 0 – 6 months. Babies who are not exclusively breastfed have a greater risk of death due to malnutrition. The failure factor for exclusive breastfeeding can be caused by various circumstances and regional factors. Objective: Knowing what are the factors that influence the failure of exclusive breastfeeding in six-month-old babies Method: The research design used is cross-sectional, using a total sampling technique. The sample used was 28 respondents who were tested using the Chi-square test. Data was collected using a closed questionnaire where respondents provided responses in the form of answer choices on the questionnaire. Data analysed using Fisher’s exact test, the p-value used was 0.05. Results: The results showed that there was no relationship between maternal age with a p-value of 0.284, education level with a p-value of 0.114, knowledge of breast milk with a p-value of 1.000, maternal employment with a p-value of 1.000 with exclusive breastfeeding failure and there was a relationship between family support with a p-value of <0.001 to exclusive breastfeeding failure. the cause of exclusive breastfeeding failure. evidenced by the existence of a relationship with a p-value <0.05. Conclusion: There is no relationship between maternal age, education, knowledge, and occupation. There is a relationship between family support and factors that influence the occurrence of exclusive breastfeeding failure.